Assessing effects of price regulation in retail payment systems - Kari Kemppainen (Bank of Finland, 2005)
This paper considers effects of price regulation in retail payment systems by applying the model of telecommunications competition by Laffont-Rey-Tirole (1998).In our two-country model world there is one retail payment network located in each country and markets are segmented à la Hotelling.We show that the optimal price under price regulation is the weighted average of pre-regulation domestic and cross-border prices where the degree of home-bias in making payments serves as the weight.Furthermore, we find that the general welfare effects of price regulation are ambiguous: gross social welfare is higher under price discrimination than under price regulation in the special case where costs of access to banking services (transportation costs) are high.However, there also exist cases where prohibitively high transaction costs make price discrimination to reduce total welfare.Finally, if transportation costs are reduced sufficiently, segmentation of payment markets is eliminated.Markets then become fullyserved as in the original Laffont-Rey-Tirole model, suggesting that price discrimination would be beneficial for welfare.
URN:NBN:fi:bof-20140807129
Keywords: D49; G28; L59; 330; payment systems; price regulation; retail payments